Reactions of Cyclic Oxalyl Compounds, Synthesis of Functionalized Hydrazono-2H-imidazol-4,5(1H, 3H)dione: Experimental Data and AM1 Calculations - Saripinar, Emin; Akcamur, Yunus; Kollenz, Gert (Asian Journal of Chemistry, 2016)
The reaction of the 4-benzoyl-5-phenylfuran-2,3-dione (1) with guanylhydrazones (2a-d) gives hydrazono-2H-imidazol-4.5-(1H,3H)-dione derivatives (4a-d) (yield ca. 30-40%). The structure of these compounds were determined by spectroscopic methods. Quantum chemical calculations were carried out for 2a-d and 4a-d by AM1 method.